Digital intraoral scanner devices: a validation study based on common evaluation criteria - Ivett Róth; Alexandra Czigola; Dóra Fehér; Viktória Vitai; Gellért Levente Joós-Kovács; Péter Hermann; Judit Borbély; Bálint Vecsei (BMC, 2022)
Abstract Background The evolution of intraoral scanners (IOSs) is rapid, and new IOSs appear on the market with different properties depending on the manufacturers. There is no uniform rating system based on a defined set of aspects that has reported in the literature that can be used to compare these devices. This validation study aimed to compare different IOSs based on objective and comprehensive parameters. Methods In this study, 12 different IOSs were examined. The IOSs that were tested in this study in order of their delivery included the 3Shape Trios 3 Pod®, Planmeca Emerald®, Straumann DWIO®, GC Aadva®, iTero Element 2®, CEREC Primescan®, Medit i500®, 3Shape Trios 4 Move®, Carestream CS3600®, 3Shape Trios 4 Pod®, Carestream CS3700®, and Planmeca Emerald S®. IOSs were evaluated in four different ways: (a)summary chart, (b)comparative assessment, (c)data based on in vitro measurements and (d)accuracy measurements. A scoring system was created to enable an objective rating of IOSs. Results The differences among IOSs were demonstrated in point scores (summary chart[max. 10 points] + weight of IOSs[max. 2.5 points] + circumference of IOSs[max. 2.5 points] + in vitro scanning time[max. 2.5 points] + pauses in data capture[max. 2.5 points] + accuracy[max. 10 points] = summary[max. 30 points]). Trios 4 Pod achieved the greatest cumulative score (23.37 points), furthermore it earned the highest points for summary chart and scanning speed. Regarding scanning continuity, the best-performing IOSs, which tied at identical point scores, were the Trios 3 and 4 Pod, Trios 4 Move, iTero Element 2, CS3600 and CS3700. The most accurate IOS was the CEREC Primescan, although it earned the lowest points of the comparative assessment (heaviest IOS). GC Aadva scored 5.73 points of a maximum of 30 points, which was the poorest result in this study. Conclusion The scoring system reflects the differences among IOS devices based on the evaluated objective parameters and can be used to help clinicians select the right IOS device. The new generations of IOSs have more special properties, and their accuracy is higher than the previous versions. Trial registration The permission for this study was granted by University Ethics Committee of Semmelweis University (SE RKEB number:108/2019).